2013
DOI: 10.1002/geot.201310013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a disc cutter force and face monitoring system for mechanized tunnelling / Ortsbrustmonitoring und Leistungsprognose bei TBM‐Vortrieben

Abstract: The loading on the tools of a TBM can usually only be estimated through the global thrust force, which gives a typical force of about 250 kN for 17′′ discs. The actual loading is however highly variable, with peak loads that can be many times the nominal load. In the present paper the development and implementation of a method is presented, which makes it possible to measure disc forces in-situ and in real time. It turns out that the measured forces are unevenly distributed over the area of the face and can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
8
0
6
Order By: Relevance
“…Entacher [7], [9], [11], [12], [13], [14], [15], [16] has shown that the geological conditions in front of a cutterhead can be described from the disc cutter force characteristics. These developments should lead to better understanding of the relationship be-…”
Section: Dclm -Disc Cutter Load Monitoringmentioning
confidence: 99%
“…Entacher [7], [9], [11], [12], [13], [14], [15], [16] has shown that the geological conditions in front of a cutterhead can be described from the disc cutter force characteristics. These developments should lead to better understanding of the relationship be-…”
Section: Dclm -Disc Cutter Load Monitoringmentioning
confidence: 99%
“…The compact nature of the camera system makes it suitable for face imaging. [4]. Der in [4] vorgestellte Ansatz des Imagestitchings leidet jedoch unter der von der Optik hervorgerufenen Verzeichnung und der perspektivischen Verzerrung einer nicht exakt lotrecht auf die Ortsbrust ausgerichteten Kamera, welche die Passgenauigkeit des anzufügenden Frames mindern.…”
Section: Photogrammetry At the Faceunclassified
“…[4]. Der in [4] vorgestellte Ansatz des Imagestitchings leidet jedoch unter der von der Optik hervorgerufenen Verzeichnung und der perspektivischen Verzerrung einer nicht exakt lotrecht auf die Ortsbrust ausgerichteten Kamera, welche die Passgenauigkeit des anzufügenden Frames mindern. Daher wird er in einem FFG-Forschungsprojekt gemeinsam mit der Geodata GmbH durch eine Anwendung photogrammetrischer Methoden erweitert, die Volumina und Tiefen von Ausbrü-chen, die Raumstellung von Klüften, entlang denen Ausbrüche vorkommen, oder beispielsweise auch Flächen von Fremdgesteinseinschlüssen bestimmbar machen.…”
Section: Photogrammetry At the Faceunclassified
See 2 more Smart Citations